The effects of using the STAD method in teaching the short story, flipping fantastic on form one students - Madhawa Nair, Subadrah (2014)
Since the year 2000 literature components have been introduced in the English language syllabus of the secondary schools in Malaysia.However until today not all teachers are aware of the possible best ways of teaching literature components effectively.This study discusses the Student Teams Achievements Divisions (STAD) method and the effect of using the method in the teaching of a short story on Form One students.The researchers used a quasi experimental design to investigate the effects of using the STAD method on the achievement of students in comprehending the short story, and their interest in learning the short story.The experimental group was taught using the STAD method and the control group was taught using the conventional method.Independent sample T-test was used to analyze the data obtained from the pre-test, post-test and the questionnaires. The findings indicate that the utilization of the STAD method significantly enhanced students’ achievement in answering questions related to setting, plot, characterization, theme and moral values compared with the control group (using the conventional method).The interest of the experimental group in reading short story was also significantly enhanced.